The wizard of Oz - Garland, Judy, 1922-1969.; Baum, L. Frank (Lyman Frank), 1856-1919.; Bolger, Ray.; Burke, Billie, 1885-1970.; Haley, Jack, 1897-1979.; Warner Home Video (Firm); Metro-Goldwyn-Mayer. (2013)
The charming film based on the popular L. Frank Baum novel, Dorothy and her dog Toto, are caught in a tornado's path and somehow end up in the land of Oz. Here she encounters some memorable friends and foes in her journey to meet the Wizard of Oz who everyone says can help her return home and possibly grant her new friends their goals of a brain, heart and courage.
Originally produced as a motion picture in 1939.
Special features: All-new feature-length documentary, The making of the wonderful wizard of Oz; commentary by historian John Fricke with the film's cast and crew; Documentaries; Outtakes; Deleted scenes; Home-movies; Sing-along feature, etc.
Based on the novel by L Frank Baum.
Judy Garland, Frank Morgan, Ray Bolger, Jack Haley, Bert Lahr, Billie Burke.
Rating: G; general audiences: all ages.
DVD9; standard version, dual-layer format; presented in a format preserving the aspect ratio of its original theatrical exhibition.